FLUORIDE LEVELS IN SALIVA AFTER CHEWING BLACK TEA CANDY (CAMELLIA SINENSIS) IN CHILDREN - Lisa Prihastari; Emha Ananda Poetra (Faculty of Dentistry, Universitas Islam Sultan Agung, 2021)
ABSTRACTBackground: Black tea has been shown to affect reducing dental plaque and increasing fluoride levels in saliva. The practice of consuming black tea in the form of candy for dental health purposes is not familiar yet. A study on the effectiveness of chewing black tea candy added with sorbitol sugar for a month on salivary fluoride levels in children aged 7-8 years can be an innovation in the prevention of dental caries. This study aims to investigate the difference in fluoride levels in saliva before and after chewing black tea candy for one month in children aged 7-8 years.Method: This is a field experimental study with double-blind and randomization. Subjects involved in this study were 44 children divided into control and intervention groups using simple random sampling. Measurement of salivary fluorine levels using the TECAN Infinite M200 Pro® UV – VIS Spectrophotometer for 3 times.Result: The results of the independent T-test showed that there were significant differences in the fluorine content in the intervention group using black tea candy on 26 November 2019, 29 November 2019, and 16 December 2019 (p<0.05).Conclusion: Chewing black tea candy is effective in increasing the amount of fluoride in saliva. Thus, it can be an alternative to anti-cariogenic agents.